The Effect of Giving Insulin Leaf Extract (Smallanthus sonchifolius) on the Reduction of the Number of Leukocytes in Wistar Rats Infected with Staphylococcus aureus - Ni’matul Murtafi’ah; Fitri Rahmi Fadhilah; Wasiyah Khusna F; Liah Kodriah (Postgraduate, University of Mataram, 2026)
This study aimed to evaluate the antibacterial activity and immunomodulatory effects of insulin leaf (Smallanthus sonchifolius) extract against Staphylococcus aureus infection in Wistar rats. The research employed an experimental design using Wistar rats divided into five groups: negative control, positive control, and treatment groups receiving insulin leaf extract at doses of 100 mg, 200 mg, and 400 mg. Leukocyte counts were measured from day 1 to day 13 following bacterial induction and treatment administration. Antibacterial activity was assessed using the well diffusion method at extract concentrations of 25%, 50%, and 75%. Statistical analysis was performed using One-Way ANOVA. The results demonstrated that insulin leaf extract significantly reduced leukocyte counts in infected rats, indicating anti-inflammatory and immunomodulatory effects. The 400 mg dose exhibited the most stable reduction in leukocyte levels throughout the observation period. Antibacterial testing showed inhibition zone diameters of 20.42 mm, 22.62 mm, and 24.90 mm at concentrations of 25%, 50%, and 75%, respectively, indicating strong to very strong antibacterial activity against Staphylococcus aureus. One-Way ANOVA revealed significant differences among treatment groups (p = 0.002) and among antibacterial concentrations (p < 0.001). These findings suggest that Smallanthus sonchifolius leaf extract possesses potent antibacterial, anti-inflammatory, and immunomodulatory properties and has potential as a natural therapeutic agent for bacterial infections caused by Staphylococcus aureus.